Scientific Substantiation of Constructive-technological Parameters of St. Petersburg Subway Underground Structures. (2017) - Frolov, Y.S.; Konkov, A.N.; Larionov, A.A.
Abstract: The introduction in St. Petersburg of new efficient designs and construction methods allows raising the pace of construction along with the reduction of the material structures. The idea requires comprehensive research, including the theoretical rationale, the model research and field observations at construction sites. The article highlights the experience of carrying out comprehensive studies with the purpose of scientific justification of the progressive design and technology solutions for the underground construction of the St. Petersburg subway. The results of research using engineering and mathematical models of the stress-strain state of complex Underground station structures are given. The practical significance of these findings is confirmed when introducing new designs of columned and vaulted stations including the design solutions adjustment of unique two-level combined transfer station "Sportivnaya". Significant scientific work in reducing negative symptoms in the process of underground structures construction is a complex research related to the implementation of excavation technologies without the sediment of the surface. The article provides information about comprehensive research to justify the feasibility of the excavation of the station tunnels and auxiliary tunnels with the application of forepoling of the roof and brow.